Dataset: Advancing towards cancer theragnostic by probing the ²²⁵Ac decay chain with ultra-high-resolution metallic magnetic calorimeter based detectors - Maurer, Kiara; Unger, Daniel; Béhé, Martin Peter; Knecht, Andreas; von Schoeler, Katharina; Hengstler, Daniel; Vitova, Tonya; Benešová-Schäfer, Martina; Fleischmann, Andreas; Gastaldo, Loredana; Wängler, Carmen; Enss, Christian; et al. (Zenodo, 2025)
This dataset contains the processed data and full analysis workflow underlying the results presented in the publication: - - Advancing towards cancer theragnostic by probing the ²²⁵Ac decay chain with ultra-high-resolution metallic magnetic calorimeter based detectors - - Files - - The dataset is organized into two archive files: - - analysis.zip: The full Python-based data reduction and analysis pipelinedata.zip: The processed spectra, OriginLab project file, and theoretical spectra - - Using the Jupyter notebooks, the ADC calibration file, and the development version of the fitfiles library included in analysis.zip, the processed data contained in data.zip can be reproduced from the individual triggered MMC signals. The processed data can be used to generate the figures in the publication. The individual triggered signals are not included here but are provided separately. - - Python Data Reduction and Analysis - - The archive analysis.zip contains the complete data analysis workflow. Inside the analysis directory, the two subfolders 2024_09-Ac225 and 2024_09-Tanzboden_Fe55 include multiple Jupyter notebooks (*.ipynb) documenting the full data-processing chain. These notebooks perform all steps required to generate the calibrated energy spectra shown in the publication, including fitting, filtering, corrections, and calibration. A development version of the fitfiles Python library, used throughout the notebooks, is included. The necessary ADC calibration file is provided in the files folder as beamtime.parquet. - - Processed Spectra and OriginLab Analysis - - The archive data.zip contains the processed spectra and the OriginLab project (*.opju) used to create the figures in the publication. These files represent the spectra derived from the analysis workflow. The included files are: - - originlab.opju: OriginLab project containing the full spectral analysis225Ac55Fe.csv: Energy spectrum of the ²²⁵Ac measurement with ⁵⁵Fe calibration 55Fe241Am133Ba.csv: Energy spectrum of the ⁵⁵Fe, ²⁴¹Am, and ¹³³Ba calibrationNucleonica.csv: Theoretical line energies and intensities exported from NucleonicaXrays.csv: Computed characteristic X-ray energies and transition probabilitiesSDD.csv: Comparison spectrum of the same ²²⁵Ac sample measured with an SDD detector - - Contact - - For questions regarding the dataset or analysis workflow, please contact the corresponding authors of the publication.
Gesehen am 19.01.2026